(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
In all domestic species, acceptable pregnancy rate with frozen-thawed semen is 20-30% through simply cervical and vaginal insemination. Researchers have proved that achievable high results can be expected only from intrauterine insemination in ewes. Unlike the cow, and goat, the cervix of ewes is a formidable barrier to penetrate for transcervical intrauterine insemination. It is not only due to the physical size of the canal and a narrow luminal diameter (even at estrus), but also due to its caudally facing eccentric series of four to eight funnel-like rings. The major aim of this study was to evaluate a comparison of transcervical and laparoscopic intrauterine artificial insemination techniques with frozen –thawed semen on the reproductive performance of ewes.58ewes of 3-4 years of age, so called Altanbulag subspecies of breed were selected and equally divided into 2 groups for the AI methods from October 15-20, 2013 in the breeding station of Research Institute of Animal Husbandry in Hongor sum, Darhan uul province. The estrus was synchronized with EAZI-BREED TMCIDR in which the progesterone content was 0.3 g. After 12 days, the CIDR were removed, PMSG of 400 and 200 IU were administrated intramuscularly per ewe. The total success of synchronization rate was 93.3%. The results has shown the possibilities of laparoscopic and transcervical AI techniques in 55.17%, 41.37% (p>0.05) of pregnancy rates respectively, with frozen-thawed semen in ewes by ultrasonography diagnosis. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 43-47